KONSENTRASI DAN MINAT BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA DI KELAS IV SEKOLAH DASAR - Maharani, Silvia; Yantoro, Yantoro; Khoirunnisa, Khoirunnisa; Ismi Mori Putra, Deka (Jurnal Muara Pendidikan, 2024)
The aim of this research is to determine the effect of concentration and interest in learning on student learning outcomes in Mathematics learning in class IV of Rengas Condong 13/I State Elementary School. Quantitative research methods (ex post facto) and purposive sampling techniques are the sampling techniques used by researchers, with data collection techniques in the form of questionnaire instruments. The research results explain: 1) the partial test results of X1 against Y found tcount > ttable, namely 5.297 > 2.086 and the Sig value 0.000 < 0.05 with a percentage of 58.4% (moderate category); 2) the partial test results of X2 against Y found tcount > ttable, namely 5.409 > 2.086 and the Sig value 0.000 < 0.05 with a percentage of 59.4% (moderate category); 3) the results of the simultaneous test X1 and X2 againts Y ound that Fcount > Ftable, namely 19.917 > 3.522 and the Sig value 0.000 < 0.05 with a percentage of 67.7% (moderate category). The results of hypothesis testing from this research reveal that concentration and interest in learning influence student learning outcomes in Mathematics learning in class IV SDN 13/I Rengas Condong.